2017
DOI: 10.1515/eng-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of reflective insulation in south east Asia

Abstract: Abstract:The objective of this research was to obtain thermal performance data for reflective insulations in a South East Asia environment. Thermal resistance data (RSI, m 2 · K/W) for reflective insulations are well established from 1-D steady-state tests, but thermal data for reflective insulation in structures like those found in South East Asia are scarce. Data for reflective insulations in South East Asia will add to the worldwide database for this type of energyconserving material. RSI were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…The study showed that the radiant barrier managed to lower the heat flux transmission by up to 70% and reduced the ceiling temperature by 8 • C during the summer days. Teh et al [16] compared the thermal performance of bubble and woven aluminium foil in two identical test cells with gable roofs. The heat flux transmission reduction for both reflective foils was roughly 80-90% compared to uninsulated roofs.…”
Section: Previous Workmentioning
confidence: 99%
“…The study showed that the radiant barrier managed to lower the heat flux transmission by up to 70% and reduced the ceiling temperature by 8 • C during the summer days. Teh et al [16] compared the thermal performance of bubble and woven aluminium foil in two identical test cells with gable roofs. The heat flux transmission reduction for both reflective foils was roughly 80-90% compared to uninsulated roofs.…”
Section: Previous Workmentioning
confidence: 99%